1984
DOI: 10.1037/0021-843x.93.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Observational conditioning of snake fear in rhesus monkeys.

Abstract: For years theorists have hypothesized on the basis of meagre evidence that observational conditioning is involved in the origins of many human and nonhuman primates* fears and phobias The present experiments provide strong support for this hypothesis by demonstrating observational conditioning of snake fear in rhesus monkeys Experiment l demonstrated the usefulness of a new index of snake fear in rhesus monkeys and, using this new measure, also demonstrated that young monkeys raised by parents who have a fear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
295
3
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(318 citation statements)
references
References 36 publications
16
295
3
4
Order By: Relevance
“…Future studies should test the relative value of social referencing from the mother versus direct experience through touching as a source of learning information. Finally, given the inconsistent results in studies on vicarious learning, it is possible that learning through observation is a relatively weak pathway to develop fear compared to conditioning or verbal information, unless stimuli that are being observed are in themselves aversive such as in Mineka's work with primates (Mineka and Cook 1993;Mineka et al 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should test the relative value of social referencing from the mother versus direct experience through touching as a source of learning information. Finally, given the inconsistent results in studies on vicarious learning, it is possible that learning through observation is a relatively weak pathway to develop fear compared to conditioning or verbal information, unless stimuli that are being observed are in themselves aversive such as in Mineka's work with primates (Mineka and Cook 1993;Mineka et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the strongest evidence supporting observational learning of fear was provided by Mineka, Cook, and colleagues Mineka 1989, 1990;Mineka and Cook 1993;Mineka et al 1984) who demonstrated clear acquisition of fear in response to fear-relevant stimuli in rhesus monkeys following exposure to a fearful model (using either live models or representations on video). Importantly, Mineka (1989, 1990) demonstrated that such vicarious fear acquisition only occurred in response to fear-relevant stimuli (e.g., toy snake, toy crocodile) and not to fear-irrelevant stimuli (e.g., flower, toy rabbit).…”
Section: Introductionmentioning
confidence: 99%
“…some environments contain features which may have been a threat to survival in our evolutionary history). Certainly it is known that evolution has provided us with a set of 'primed' emotional responses which result in rapid selective learning and great difficulty in extinguishing such responses (see for example the seminal work of Mineka et al, 1984). Not surprisingly, therefore, Kobayashi et al (2015) note that some people with biophobia (Kellert, 1993) report a strong dislike for natural environments, this includes specific phobias such as arachnophobia.…”
Section: Nature and Hrv Research Discussionmentioning
confidence: 99%
“…Pavlovian) conditioning process in which the emotional expression of the person being observed acts as an unconditioned stimulus (UCS) for the observer and the object eliciting the emotional response is the conditioned stimulus (CS+) (Mineka & Cook, 1993;Olsson & Phelps, 2007). However, most studies have not adequately isolated this mechanism because the emotional facial expression is not the only UCS in the learning experience (Merckelbach et al, 1991;Mineka & Cook, 1993;Mineka, Davidson, Cook, & Keir, 1984;Olsson & Phelps, 2004). For example, an individual with no prior fear can develop a fear of snakes after observing someone else's fearful reaction (Mineka & Cook, 1993).…”
Section: Basic Models Of Classical Conditioning and Observational Leamentioning
confidence: 99%